Normalização e barreiras não tarifárias: uma análise da influência das normas socioambientais de gerenciamento no comércio internacional - Cajazeira, Jorge Emanuel Reis (2008)
Commerce and standardization jointly improve the efficiency of the international trade flows enhancing society welfare since a long time. In fact, since 1945 the ISO – International Organization for Standardization works to create a full range of norms that make the commerce feasible. However, during the globalization process the certifiable management standards arise from the need of assurance quality to allow outsourcing production with the development of the ISO 9000 series. The concept of management standards rapidly migrate to other fields of the management like environmental and now days to social issues. The current text initially analyses the reasons for the raisin success of Management System Standards (MSS), like the growing environmental awareness and all the changes in trade during globalization age. After that it discusses the demands and influences of the new economy: the knowledge society. Considering these contexts some empirical basis in terms of statistical data analysis was found to help understanding the behavior change among developing and develop countries regarding the use of socio environmental standards. Some evidence was found that the developing countries have change from their skepticism in see the MSS as a non-tariff trade barrier to consider MSS as a tool to legitimization to facilitate trade of goods. For the other hand the develop countries recently starts being contrary the creation of new MSS. A possible explanation found was the knowledge societies that transfer the manufacturing of goods to countries with low salary cost and few environmental regulations that helps the global cost reduction and simultaneously keep inflation down and raise the buyer power of developed countries’ consumers.